Después del Conectar igualdad Tecnobiografías juveniles en el Gran La Plata - Benítez Larghi, Sebastián (Gran La Plata, 2022)
After "Conectar Igualdad": Juvenile Technobiographies in Greater La Plata. After "Conectar Igualdad" studies a digital inclusion policy from the perspective of its beneficiaries. Its chapters trace the different meanings that the appropriation of digital technologies acquires throughout the lives of the youth. From a socio-anthropological perspective and through the reconstruction of technobiographies inscribed in different contexts, this work goes through the winding paths of technological appropriation, in relation to which subjects, objects and policies interrelate in multiple ways. It thus captures the net of adaptations, negotiations and resistances that young people weave with digital technologies, without losing sight of the stark inequalities that mark their social, educational and labor trajectories.